Discovering active sites in peptide Ala–Val–Thr–Phe that counter 2, 2-azobis(2-methylpropanimidamidine)dihydrochloride-induced oxidative stress in HepG2 cells. Issue 41 (26th June 2020) - Liang, Jiaxi; Wang, Qin; Liu, Jianliang; Huang, Guozhong; Liang, Churong; Liu, Huifan; Ma, Lukai
Abstract : The potential mechanism underlying the cytoprotective effects of the Ala–Val–Thr–Phe (AVTF) peptide derived from edible Dendrobium aphyllum was co-incubated with Lactobacillus amylolyticus . Abstract : The Ala–Val–Thr–Phe (AVTF) peptide derived from edible Dendrobium aphyllum was co-incubated with Lactobacillus amylolyticus in a previous study. The aim of the present study was to further examine the antioxidative and protective effects of the AVTF peptides through the analysis of free-radical quenching in HepG2 cells subjected to 2, 2-azobis(2-methylpropanimidamidine)dihydrochloride (AAPH)-induced oxidative stress and to determine the active sites within the peptide. Variations in intracellular malondialdehyde levels indicated that these peptides protect HepG2 cells by preventing ROS attack and lipid peroxidation. Antioxidant enzymes and Nrf2 were downregulated in AVTF-treated but not in AAPH-treated HepG2 cells, whereas the electrically sensitive Keap1 was not susceptible to free radical-induced damage after AVTF treatment. However, this did not result in the activation of the Nrf2/Keap1 signaling pathway, thus indicating that one potential mechanism by which AVTF maintains homeostasis in HepG2 cells is by directly scavenging free radicals. Furthermore, quantum chemical calculations and the assessment of electronic-related properties associated with antioxidant activity revealed that the active sites of AVTF included N9 –H11, which was further confirmed by the assessment of ROS levels in methylated AVTF-treated cells. The results of this study provide valuable insights into the active site N9 –H11 in the Ala residue of AVTF, which influences the antioxidant activity of the peptide.